Sistem Informasi Manajemen Aset Berbasis Web Pada PT Terentang Maju Jaya - Suryani, Lilis; Devitra, Joni (LPPM Universitas Dinamika Bangsa, 2022)
PT Terentang Maju Jaya is a company owned by Terentang Baru Village which is a unit of Terentang Baru Village-Owned Enterprises (BUMDesa). So that the assets owned by this company are assets belonging to the Terentang Baru Village which are required to report assets to the Terentang Baru Village government every year. In managing and reporting assets, they still use the manual method, namely by using Microsoft Office Excel so that it often causes several problems including data loss, employees cannot report assets wherever they are and the slow recording process causes ineffective and efficient management and reporting of assets. One way to optimize management and reporting is by using a web-based information system. This research starts from analyzing and designing a system that is carried out at the planning, procurement, asset data, and asset deletion stages. This research produces a prototype system that describes the functional planning, procurement, asset data, and asset deletion at PT Terentang Maju Jaya. The system design model uses UML (Unified Modeling Language), namely: use case diagrams, class diagrams and activity diagrams. This research produces a prototype web-based asset management information systemthat features the login menu, asset planning, asset procurement, asset receipt, changing and adding to the asset list, asset placement, asset data search, and asset reporting. This research still needs to be developed so that it can be used and applied to PT Terentang Maju Jaya and it is hoped that the next research can design a system that is more complete and easier to apply to PT Terentang Maju Jaya.